KERANGKA KERJA HEUTAGOGI UNTUK MENINGKATKAN PEMBELAJARAN DAN PENGALAMAN BELAJAR MAHASISWA DALAM MATA KULIAH KETERAMPILAN BERBICARA - Saleh, Muhammad; Baharman, Baharman; Fitri, Sakinah (Fakultas Teknik Universitas Negeri Makassar, 2023)
A heutagogical approach in learning speaking skills that is designed explicitly in accordance with heutagogical principles. A model design with a heutagogical framework integrated with language skills in the speaking skills aspect is taught to students to improve students' learning and learning experiences in speaking skills courses. This type of research carried out developed the DBR (design based research) model or what is better known as design-based research. The data in this research is grouped into two types, namely qualitative data and quantitative data. Specifically, what this article wants to achieve is qualitative data as a form of information related to the heutagogical approach to speaking skills. Based on the research results, it shows that the heutagogical framework in learning and improving student learning outcomes in speaking skills courses refers to identifying the variety/type of speaking skills you want to learn, determining the learning method/process using mobile media and social media. As a conclusion in this research, students are responsible for their own learning and determine and control themselves what they will learn, when and how they will learn, especially by using mobile media or social media.